Canyon de Chelly, its people and rock art - Grant, Campbell, 1909-1992 (University of Arizona Press, 1978)
With the exception of the Grand Canyon itself, none of the great gorges of the American Southwest is more uniquely beautiful than Canyon de Chelly, with its sheer red cliffs and innumerable prehistoric Indian dwellings. Of all the important centers of prehistoric Anasazi culture, only this magnificent canyon shows an unbroken record of settlement for more than 1,000 years. In this liberally illustrated book, rock art authority Campbell Grant examines four aspects of the spectacular canyon: its physical characteristics, its history of human habitation, its explorers and archaeologists, and its countless rock paintings and petroglyphs. Grant surveys 96 sites in the two main canyons and offers an interpretation of the rock art found there.